Інтерполювання звичайних диференціальних операторів - Литвин, О.М. (Видавничий дім "Академперіодика" НАН України, 2007)
Basic statements of the theory of the approximation of ordinary differential operators by other ordinary differential operators are given. Approximated and approximating operators are equal on a given system of functions (functional knots).